Ficción y verdad según la teoría literaria de Alfonso Reyes - Malavé González, Mercedes (El Colegio de México, 2012)
In his Deslinde. Prolegómenos para una teoría literaria, Alfonso Reyes describesthe relationship between metaphysical being and poetic fiction as the keyto understanding the ethical dimension of fiction. In his paper it is clearthat the notion of mimesis is not reduced to cannons of formal imitation oflogos, or reality, and that artistic creation consists of a dia-logos that can leaveroom for forms that are non-existent but not far from being. Reyes harmonizesthe poetic conceptions of Aristotle and Plato in his attempt to definethe relationship between truth and fiction.